Vietnamese male labour trafficking: A sad reality that requires our attention - Desmarteaux-Houle, Audrey (Université d'Ottawa | University of Ottawa, 2012)
One of the biggest myths of our world today is that slavery is a thing of the past and human trafficking occurs only in the third world. In fact, modern day slavery is a far more common occurrence than believed and it exists throughout both the developed and under developed world under the guise of human trafficking. Trafficking in persons is the third largest criminal industry in the world. It follows illegal drugs and arms trafficking. No country is immune to this problem, including Vietnam. Vietnam is one of the fastest growing economies in the world, yet employment opportunities are limited and so the Vietnamese seek work, wherever it can be found, even if it means having to work abroad. In Vietnamese culture, males are considered the breadwinner for the family and they will migrate legally, or illegally, in order to fulfill this role and provide for themselves and their families. Most Vietnamese males lack understanding of migration laws and therefore turn to brokers or legitimate recruitment agencies for help in this process of finding work abroad. Many of these middlemen have unethical practices that lead to corruption and abuses within the system. Many Vietnamese dealing with middlemen are promised incredible salaries and jump on the offers not knowing what to expect. Once abroad, their human rights are often violated by their employers and they are caught in the middle of labour trafficking circles, unable to reach for help. Gender issues compound the problem since in Vietnamese culture, men are expected to be strong. As a result, males often refuse to admit to being victimized and labelled as victims thereby placing themselves outside of the help that they need and might otherwise receive. This frequently ends with Vietnamese adult males being deported rather than securing justice for the abusers, thus perpetuating the problem of human trafficking. This paper seeks to understand the issue of male labour trafficking in Vietnam, and puts forward potential solutions, as well as key recommendations, for addressing these issues in Vietnam.The author is aware that the proposed solutions are by no means a complete remedy for the problem of trafficking of males for the purpose of labour in Vietnam. However, it is hoped that these recommendations might contribute to the dialogue and assist the organizations who have assumed the courageous task of solving this complex and abhorrent crime of our modern times.